Metal based rapid prototyping for more complex shapes - Ribeiro, A. Fernando (1996)
In the last 18 months a new Rapid Prototyping process involving direct deposition of metal has been under development at Cranfield University. The process entails the use of a Gas Metal Arc fusion welding robot which deposits successive layers of metal in such way that it forms a 3D solid component. A solid model is first drawn using a CAD system, then data indicating the kind of layers and dimension is incorporated and the solid is automatically sliced. This slicing routine also generates reports on the welding time and conditions for the production of the component and automatically generates the robot program. Depending on the complexity of the component the time from drawing the component to being ready to press the start button of the robot to make the component can take less than two hours. An example of a component which was generated to test the system is described here in order to illustrate how the process is operated, the quality of the component, and the productivity which may be expected.